Pengaruh Komisaris Independen, Pajak Tangguhan dan Laba Bersih Terhadap Manajemen Laba dengan Tax Avoidance sebagai Variabel Intervening pada Perusahaan Sub Sektor Makanan & Minuman di Bursa Efek Indonesia Periode 2015 – 2019 - Telly Zuvilla; Yunan Surono (Universitas Batanghari Jambi, 2022)
This study is to look at the influence of independent commissioners, deferred tax and net profit on earning management with tax avoidance as intervening variables in food and beverage sub-sector companies in the Indonesia Stock Exchange period 2015 – 2019. The research samples used are sub-sectors of food and beverages on the Indonesia Stock Exchange during the 5-year observation period starting from 2015 – 2019. There are 27 companies, which have complete financial statements and which have complete research indicator reports in the annual financial statements during the research period of 17 companies, and which use rupiah currency units as many as 16 companies and which have a positive net profit during the research period of 11 companies. This study uses purposive sampling and data analysis techniques using microsoft Excell and SPSS 22.0 software. path analysis. The results showed that; 1) Independent variables independent commissioner, deferred tax and net income against tax avoidance simultaneously all free variables affect bound variables while partially nothing affects the variable tax avoidance. 2) independent variable independent commissioner variables, deferred tax and net profit to earning management, simultaneously all free variables have a significant effect on bound variables whereas partially only net profit variables affect profit management variables.. 3) Tax avoidance variables have no effect on earning management variables. 4) Independent commissioner variables, deferred taxes and net income on profit management with tax avoidance as intervening variables have a total influence of 1.277%, which is greatly influenced including weak.